2014
DOI: 10.1002/jmri.24745
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis lesion geometry in quantitative susceptibility mapping (QSM) and phase imaging

Abstract: Purpose To demonstrate the phase and QSM patterns created by solid and shell spatial distributions of magnetic susceptibility in MS lesions. Materials and Methods Numerical simulations and experimental phantoms of solid- and shell-shaped magnetic susceptibility sources were used to generate magnitude, phase, and QSM images. Imaging of 20 consecutive MS patients was also reviewed for this IRB-approved MRI study to identify appearance of solid and shell lesions on phase and QSM images. Results Solid and shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 30 publications
1
69
2
Order By: Relevance
“…39 One previous study demonstrated a vast difference among QSM and phase results, wherein the authors concluded QSM was superior to depiction of spatial susceptibility patterns in MS lesions. 15 Similarly, we found wide-ranging differences in lesion classification based upon QSM versus phase images (data not shown). A major contributing factor to the difficulty of identifying and quantifying rim+ lesions has been the choice of susceptibility reference tissue.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…39 One previous study demonstrated a vast difference among QSM and phase results, wherein the authors concluded QSM was superior to depiction of spatial susceptibility patterns in MS lesions. 15 Similarly, we found wide-ranging differences in lesion classification based upon QSM versus phase images (data not shown). A major contributing factor to the difficulty of identifying and quantifying rim+ lesions has been the choice of susceptibility reference tissue.…”
Section: Discussionmentioning
confidence: 55%
“…17 We identify QSM rim+ lesions as having a rim of iron based upon the susceptibility gradient between the rim and core regions. Support of this approach is based upon three factors: 1) known pattern of demyelination found within chronic active MS lesions (dense loss of myelin in core), 3, 6, 12 2) histological studies demonstrating that GRE can detect iron within activated m/M at the edge of chronic active MS lesions 1, 3, 4, 11, 14, 15 and 3) our own data, demonstrating a decrease in both susceptibility and MWF from rim to core, which can only be explained by iron deposition. Thus we conclude that iron is contributing, at least in part, to the signal at the rim but importantly, we are not quantifying the absolute extent that iron or myelin is contributing to the QSM signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(11, 12) Since phase is a non-local measure, phase contrast can be influenced by the magnetic susceptibility of adjacent tissues, orientation of the head in the magnetic field, and the shape of a lesion, resulting in unreliable quantification of phase shifts and artifacts such as false rims around lesions. (13)…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, QSM improves the detection and spatial distribution of subtle iron deposition that are not seen on conventional T2* imaging. 20 This makes it possible to describe patterns of iron deposition within lesions (eg. nodular vs. ring-like) based on their 7T MRI findings, which have been rarely described in the literature.…”
Section: Introductionmentioning
confidence: 99%